Writing Family History As A Local Historical Study - Kamil, Chaidir Sastra (Universitas Pendidikan Indonesia, 2023)
This study aims to uncover how the meaning of Family in the cultural history of the Sundanese community is known to be closely related to social life. The culture that exists in the Sundanese community is considered to have a fairly strong belief and participation with the ancestors but with the presence of Islam in the archipelago culture makes the Sundanese people begin to adapt slightly to the presence of Islam. The Sundanese people also consider that the Family is a place in knowing the role of their ancestors in the past and providing education and morals for later generations, and the role in historical science is also very important in interpreting Pancaki because it provides us with information starting from knowing the history of our own Family, this is also directly related to how Local History was formed in each region and region respectively and must be preserved in each generation of it.